Answer:
see explanation
Explanation:
Either both equations are equal or are multiples of each other
As an example consider the 2 equations
4x - y = 2 → (1)
- 12x + 3y = - 6 → (2)
Multiply (1) by - 3
- 12x + 3y = - 6 → (3)
Subtract (3) from (2) term by term
(- 12x - (- 12)x) + (3y - 3y) = (- 6 - (- 6)), that is
(- 12x + 12x) + 0 = - 6 + 6
0 = 0
This indicates the solution has infinite solutions
let x = k, k is a real number then from (1) y = 4x - 2 ⇒ y = 4k - 2
Thus (k, 4k - 2) will generate solutions to the system of equations